A Correlation Study of Multicultural Personality, Ethnic Identity, and Emotional Regulation among Guidance and Counseling PPG Students - Suciani Latif; M. Fiqri Syahirl; Akhmad Harum (Bisma The Journal of Counseling, 2025)
This research aims to examine the influence of multicultural personality and ethnic identity on the emotional regulation of students in the Guidance and Counseling Teacher Professional Education Program. This study uses a correlational quantitative approach. The research sample consisted of 90 students from professional teacher education programs who were selected taking into account gender, ethnicity and age diversity. Data were collected using three instrument scales: Multicultural Personality Scale (40 items), Ethnic Identity Scale (17 items), and Emotion Regulation Scale (30 items). The validity and reliability of all scales have been tested using the Rasch Model, showing valid results and very high reliability (Cronbach Alpha > 0.80). Data analysis was carried out using multiple correlation. The results of the analysis show that simultaneously, multicultural personality and ethnic identity have a significant effect on the emotional regulation of PPG BK students (Sig. = 0.00 < 0.05), with both predictors contributing substantial variance to emotional regulation abilities. The implications of this research indicate that developing multicultural awareness and strengthening ethnic identity in prospective guidance and counseling teachers can improve their ability to regulate emotions. Increasing this competency is important to support the effectiveness of guidance and counseling services in the context of multicultural education. It is hoped that these findings can become the basis for developing a PPG BK curriculum and training program that integrates multicultural competence and emotional regulation skills.